A Polymeric Dye of Aqueous Disperse Violet 17-Based Polyurethane Dispersion - Hu, Xianhai; Zhang, Xingyuan; Liu, Jin; Dai, Jiabing (Asian Journal of Chemistry, 2013)
A polymeric dye, aqueous disperse violet 17-based polyurethane dispersion (PU-DV17), was synthesized depending on a modified acetone process. The structure of PU-DV17 was confirmed by FT-IR and UV-visible analysis. Due to presence of well-known anthraquinone in PU-DV17, this polymeric dye exhibited intriguing optical behaviour in aqueous solution. The fluorescence intensity of PU-DV17 emulsion was enhanced greatly with contrast to that of DV17. It was found that the fluorescence intensity of PU-DV17 emulsion would decline along with increasing temperature between 20 ºC and 40 ºC and enhance along with increasing temperature between 40 ºC and 90 ºC. The fluorescence of PU-DV17 emulsion was very stable and was not sensitive to hydroquinone quencher.